Urdu language ideologies and Pakistani identity - Hopf, Arian (Language ideologies and the vernacular in colonial and postcolonial South Asia, 2023)
Pakistan was founded in 1947 as a separate country from India and struggled for an autonomous identity right from its beginning. It was founded as a country for the Muslims of undivided India. Yet, most supporters of the Pakistan movement came from outside the eventual territory. Thus, the question of what unites this country was posed right after 1947 and seems to remain unanswered to date. Without doubt, Islam served as a central aspect for defining Pakistani identity. However, the political category of Muslim was still new, and soon after partition from the “Hindu”-India, it lost its appeal while ethnic or linguistic bonds were increasingly emphasised. Another essential part of the identity of Pakistan hinges on its distinction from India - a country which now inherited most of the geographical places connected to Muslim history in the subcontinent. Urdu was declared Pakistan’s national language - a language that had no dissemination as the first language in the territory of Pakistan but was spread in the area of Delhi and Uttar Pradesh, now part of the Indian territory. Despite the essentiality of distinguishing its identity from India, Pakistan also could not eliminate its historical and linguistic link to India - a dilemma that shall be analysed in this chapter.